Temperature and Transverse Expansion of Fireballs in Pb+Pb Collisions at the LHC - Ivan Melo; Boris Tomasik (Communications - Scientific letters of the University of Zilina, 2014)
We analyze hadron transverse momentum spectra from Pb+Pb Collisions recorded by the LHC detector ALICE. As the theoretical model we use a Monte Carlo model which includes production and decays of resonances. The transverse expansion of the fireball is shown to be stronger and the freeze-out temperature higher than in similar collisions at RHIC, where collision energy is more than ten times lower.